Time to initiation of adjuvant chemotherapy in patients with rapidly proliferating early breast cancer. Issue 14 (September 2015) - Farolfi, Alberto; Scarpi, Emanuela; Rocca, Andrea; Mangia, Anita; Biglia, Nicoletta; Gianni, Lorenzo; Tienghi, Amelia; Valerio, Maria Rosaria; Gasparini, Giampietro; Amaducci, Laura; Faedi, Marina; Baldini, Editta; et al.
Abstract: Aim: To evaluate the optimal time interval from definitive surgery to commencing chemotherapy in early breast cancer (EBC). Patients and methods: The relationship between time to initiation of adjuvant chemotherapy (TTC), calculated in weeks, and disease-free (DFS) or overall survival (OS), was assessed in 921 EBC patients with rapidly proliferating tumours (thymidine labelling index >3% or G3 or Ki67 >20%), randomised in a phase III clinical trial (NCT01031030) to receive chemotherapy with or without anthracyclines (epirubicin → cyclophosphamide, methotrexate and fluorouracil (CMF) versus CMF → epirubicin versus CMF). DFS, OS and 95% confidence intervals (95% confidence interval (CI)) were calculated by the Kaplan–Meier method. Multivariate Cox analysis was performed in relation with nodal involvement, oestrogen receptor and human epidermal growth factor receptor 2 (HER2) status, Ki67 value, type of adjuvant chemotherapy, menopausal status and tumour size. Results: At a median follow-up of 105 months (range 2–188), a prolonged TTC resulted in a significant increase in the risk of relapse: hazard ratio (HR) 1.15 (95% CI 1.02–1.30, p  = 0.019). Using a backward elimination procedure, TTC, tumour size and nodal involvement remained significantly associated with DFS. A time-dependent receiver-operating characteristic (ROC) curve analysis was subsequently utilised to evaluate the best cut-off for TTC, identifying 7 weeks as the best threshold for longer OS ( p  = 0.043): 8-year OS 88% (95% CI 85–90) for patients with a TTC <7 weeks and 78% (95% CI 68–87) for the other group. Conclusions: Our results confirm that a shorter TTC may reduce relapses and possibly also improve clinical outcome in patients with highly proliferating EBC.